A Case for Including Economic, Social and Cultural Rights in the New Zealand Bill of Rights Act 1990 - Opie, Joss (Victoria University of Wellington Law Review, 2012)
Economic, social and cultural rights are fundamental human rights, but New Zealand domestic law does not recognise them as such. This article discusses some of the difficulties this omission creates for the protection of these rights, and critiques the reasons for not including them in the New Zealand Bill of Rights Act 1990. It argues that economic, social and cultural rights should have the same legal status in New Zealand as civil and political rights: that is, justiciable rights which are also directly relevant to statutory interpretation, and law and policy-making.